Live to 70 years and older or suffer in silence: understanding health insurance status among the elderly under the NHIS in Ghana - Fenny, A.P. (My University, 2017)
Ghana has introduced a National Health Insurance Scheme (NHIS). Embedded in the NHIS is a policy to exempt poor and vulnerable groups from premiums and user fees. There has been some debate as to why the start-off age for exemption among the elderly is 70 years. Ghana has a shorter life expectancy than middle- and high-income countries and its current age of retirement is 60 years. This study explores the financial and social implications of continuing to charge premiums to people aged 60 to 69 years. Based on the analysis of data from a representative household survey, it is recommended that the exemption policy should be expanded to include all vulnerable elderly persons, regardless of age.
Keywords: Elderly; enrollment; exemption policy; health insurance; household survey